Long-Run Money Demand in Large Industrial Countries : Volume 38 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1991)
The long-run properties of money demand functions in the large industrial countries are examined under the hypothesis that the long-run functions have been stable but that the dynamic adjustment processes are more complex than those represented in most earlier models. The results broadly support this hypothesis, but for certain aggregates they also call into question some basic hypotheses about the nature of the demand function, including, notably, that of homogeneity with respect to the price level.